(untitled) (International Journal of Environmental Sciences, 2025)
An Easy, sensitive, specific, and precise RP-UPLC method for the pharmaceutical dose estimation of Bevacizumab in injectable dosage form. Chromatogram was run through ACQUITY UPLC HSS C18 Column, 130A, 1.7 um, 2.1 mm X 100 mm. Mobile phase containing 0.1% OPA: Acetonitrile taken in the ratio 60:40 was pumped through column at a flow rate of 0.3ml/min. Temperature was maintained at 30.7°C. Optimized wavelength selected was 215.0nm. Retention time of Bevacizumab was found to be 0.945 min. %RSD of the Bevacizumab were and found to be 0.8. %RSD of Method precision of Bevacizumab was found to be 0.2 %Recovery was obtained as 99.75% for Bevacizumab. LOD, LOQ values obtained from regression equation of Bevacizumab were 0.05, 0.16. Regression equation of Bevacizumab is y = 11549x + 1531.9. Retention times were decreased and that run time was decreased, so the method developed was simple and economical that can be adopted in regular Quality control test in Industries.